Factors Affecting Employee Engagement: Case Study at Bank Rakyat Indonesia - Satria, Dicky; Alghani, Alghani; Agustania, Virgitha Isanda; Maharani, Anita (Syntax Literate, 2025)
This study analyzes the effect of perceived organizational support, digital culture, and digital transformation on employee engagement with self-efficacy as a moderator. The concepts discussed and elaborated in this study highlight the necessity of each antecedent; therefore, we adopt a quantitative research design. However, this study was conducted among Bank Rakyat Indonesia (BRI) employees across Indonesia who were randomly selected. Respondents in this study were 423 employees of BRI who voluntarily completed the questionnaire survey distributed via an online form. The collected data were then further processed using a partial least squares structural equation modelling approach. The results of this study confirmed all hypotheses. Therefore, employee engagement in the BRI environment, as represented by respondents, was influenced by perceived organizational support, digital culture, and digital transformation, with self-efficacy moderating. This indicates that the company's policies and treatments depend on whether a person can follow them or be part of them.